The Effects of Ethanol Extract of Vernonia Amygdalina on Optic Nerve Damage Based on Histopathological Overview, Ganglion Cell Density, and Average Apoptosis in Diabetic Rat Models - Aulia Purnama Effendi; Masitha Dewi Sari; Bobby Ramses Erguna Sitepu (Journal of Social Research, 2026)
Diabetes mellitus (DM) is one of the most commonly diagnosed degenerative conditions worldwide, often resulting in significant negative impacts on the optic nerve due to chronic hyperglycemia. Hence, there is a need for additional therapeutic modalities capable of reducing or even preventing the effects of DM on optic nerve damage, such as the African plant Vernonia amygdalina, which is rich in medical benefits like anti-inflammatory and antioxidant properties. This study aims to determine the effects of ethanol extract of Vernonia amygdalina on parameters related to optic nerve damage in a diabetic rat model. This experimental animal-based study was conducted on five groups of diabetic Wistar rats (7 rats per group) induced with streptozotocin and nicotinamide, with ethanol extract intervention at doses of 100–300 mg/kg body weight per day. The intervention was carried out for four weeks using Vernonia amygdalina ethanol extract, followed by evaluation of histopathological characteristics, ganglion cell density, and average apoptosis in the optic nerve. A significant increase in average apoptosis (P < 0.05) was observed in the control group (74.33 ± 4.03) compared to the P2 group (200 mg/kg body weight per day; 47.50 ± 5.96) and the P3 group (300 mg/kg body weight per day; 22.00 ± 1.67), a finding nearly equivalent to that of the untreated sham group (19.67 ± 3.33). Furthermore, administration of Vernonia amygdalina extract maintained normal axons and Schwann cells only in the P3 group, with ganglion cell density appearing loosely packed to dense at doses of 100–300 mg/kg body weight per day. Overall, Vernonia amygdalina extract had a positive effect on the optic nerve in diabetic rats, as evidenced by the average apoptosis findings and histopathological evaluation.